A CRITICAL ANALYSIS OF THE CONCEPT OF WUJUD IN ISLAMIC PHILOSOPHY: IBN ARABI'S VIEW - Bai Rohimah; Suhari (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
This research examines the concept of Wahdat al-Wujud introduced by Ibn Arabi in the context of Islamic philosophy. This term refers to the idea that everything that exists is a manifestation of one absolute form of God. This research aims to critically analyse the impact and implications of this thought on the development of Islamic philosophy and theology. Using the literature method, this research explores the interrelationship between the concept of Wahdat al-Wujud and the practice of mysticism in Islam, as well as identifying the criticisms that arise from the orthodox view. The results show that although controversial, Ibn Arabi's thought has made an important contribution in enriching the discussion and understanding of the essence of existence in Islam. The findings emphasise the importance of historical and intellectual context in appreciating Ibn Arabi's contribution to the Islamic philosophical tradition.